The Correlation between Coping Mechanisms and Resilience with Academic Dishonesty in Medical Students - Prananda, Faadhilah Widya; Muktamiroh, Hikmah; Bahar, Meiskha; Irmarahayu, Agneta (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
Academic dishonesty is the most common violation of academic integrity. One factor that influences academic dishonesty is self-reliance, which includes coping mechanisms and resilience. This study aims to determine the correlation between coping mechanisms and resilience with academic dishonesty in Medical students. This study was an observational analytic study with a cross-sectional method. The respondents were preclinical stage students in the Faculty of Medicine. This study utilized stratified random sampling with a total sample of 229 students. The data type used in this study was primary data collected using a questionnaire. Data analysis in this study used the Chi-Square test. Based on the results of statistical tests, the majority of coping mechanisms in Medical students was emotion-focused coping faced by 127 (55.5%) students, 182 (79.5%) students had high resilience, and 203 (88.6%) students had low academic dishonesty. Coping mechanism and academic dishonesty obtained a p-value of 0.552, while resilience and academic dishonesty obtained a p-value of 0.003. Thus, it can be concluded that there was no correlation between coping mechanisms and academic dishonesty. However, there was a correlation between resilience and academic dishonesty in Medical students. The implication of this study was the importance of resilience as one of the academic honesty of student characters.